Quality, Range, and Legibility in Web Sites Related to Orofacial Functions - Correa,Camila de Castro (2013)
Introduction  Plenty of information about health is available on the Internet; however, quality and legibility are not always evaluated. Knowledge regarding orofacial functions can be considered important for the population because it allows proper stimulus, early diagnosis, and prevention of the oral myofunctional alterations during early infancy. Objective  The aim was evaluate the quality, legibility, and range of Web sites available in Brazilian Portuguese regarding the orofacial functions. Methods  Selected Web sites with information directed to parents/caregivers of babies regarding breast-feeding, feeding after 6 months, deleterious oral habits, and breathing and speech were studied. The Web sites were evaluated through the application of Flesch Reading Ease Test and aspects of the Health on the Net (HON) modified code (HONCode); the range of the subjects addressed was compared with other aspects of infant development. Results  From the access of 350 pages of the Internet, 35 Web sites were selected and 315 excluded because they did not meet the inclusion criteria. In relation to legibility, Web sites scored an average of 61.23% in the Flesch Test, and the application of the modified HONCode showed an average of 6.43 points; an average of 2.49 subjects were found per Web site evaluated, with information on breast-feeding being more frequent and subjects such as breathing and speech less frequent. Conclusions  Web sites that deal with orofacial functions presented standard legibility classification. Only half of the ethical principles were considered by the modified HONCode in their majority, and most addressed subjects after “breast-feeding” were presented with restricted range.